Temporal modulation of gene expression in a controlled Schistosoma mansoni human infection model - Li, Dawei; Jiang, Chuan; Zhu, Wenyu; Houlder, Emma L.; Stam, Koen A.; Koopman, Jan Pieter R.; Langenberg, Marijke; Kavishna, Ranmali; Torkzadeh, Sara; Andersson, Björn; Persson, Josefine; Kalyanasundaram, Aravindan; et al. (Frontiers in Immunology, 2025)
BackgroundSchistosomiasis is caused by parasitic blood flukes of the genus Schistosoma. Despite ongoing mass drug administration efforts, the disease remains a major public health burden in endemic regions. A better understanding of early host responses to schistosomiasis is critical for developing effective vaccines and therapeutics.MethodsWe conducted a longitudinal transcriptomic study of peripheral blood samples from 30 Schistosoma-naïve volunteers participating in two controlled human infection trials with male- or female-only S. mansoni cercariae. Blood was collected at six time points over 20 weeks post-infection. Whole-transcriptome RNA sequencing and integrative analyses, including differential gene expression, gene set enrichment, protein interaction networks, co-expression clustering, and immune module profiling, were employed to characterize temporal modulation of genes related to immune responses.ResultsRobust and highly time-dependent transcriptional responses were observed, peaking at Week 4 post-infection. Differential gene expression and pathway analyses revealed activation of immune responses, including type I and II interferon signaling, chemokine-mediated pathways, and antigen presentation. Notably, both Th1 and Th2 signatures were evident at Week 4. Key immune hubs included IFNG, TNF, and IL1B, along with transcriptional regulators such as STAT1 and IRF7. Blood transcription module analysis further highlighted transient activation of interferon and plasma cell-related responses.ConclusionsThis study provides a comprehensive transcriptional map of early host responses to S. mansoni infection in humans. The findings underscore the central role of interferon pathways, early mixed Th1/Th2 polarization, and inflammation-associated gene signatures in shaping host response to S. mansoni infection. These insights may inform the rational design of vaccines and biomarkers for schistosomiasis.